Understanding strategic stakeholder management - Tommaso, Silvia Ferraz Nogueira De (2024)
Our research aims to understand how strategic stakeholder management drives a competitive advantage. The thesis objectives are (1) to understand how companies develop a value creation system for multiple stakeholders, (2) to understand the micro-foundations of a stakeholder management capability, and (3) to understand how stakeholder management drives a new business strategic positioning. For that, we aim to cover the main elements of a business competitive advantage model: value creation and appropriation mechanisms, resources and capabilities, and positioning. For that, we applied qualitative, exploratory multiple case study. We interviewed 55 people from 11 different companies. We designed our research into three papers. Paper 1, Stakeholder Value Creation System: Understanding the Process, aimed to understand how companies develop a value creation system for multiple stakeholders. Paper 2, Micro-foundations of Stakeholder Management Capability, aimed to investigate how top managers develop and coordinate specific capabilities to create value with multiple stakeholders simultaneously and achieve performance. Paper 3, Stakeholder Positioning Strategy: A New Strategic Positioning, aimed to understand how strategic stakeholder management drives a new strategic positioning. Our data revealed that strategic stakeholder management is changing companies competitive advantage model. The Strategic Stakeholder Management Model embraces the development of a Stakeholder Value Creation System, Stakeholder Management Capability, and Stakeholder Strategic Positioning. The model suggests an ongoing process. We contribute to Stakeholder Theory and Resource-based Theory by explaining how combining both theories may help managers manage their companies facing societal grand challenges.